Sarcopenia as a Predictor of Mortality in a Cohort of Elderly Patients Undergoing Endoscopic Retrograde Cholangiopancreatography - Giacomo Mulinacci; Clara Benedetta Conti; Alberto Savino; Davide Gandola; Davide Ippolito; Roberto Frego; Alessandro Ettore Redaelli; Marta Maino; Marco Emilio Dinelli (Life)
Background and aims: Despite technical advances, endoscopic retrograde cholangiopancreatography (ERCP) is associated with complications and potentially lethal outcomes. Sarcopenia, a complex syndrome mainly associated with aging, has been recognized as a predictor of poor surgical outcomes. Thus far, the impact of sarcopenia on ERCP remains unknown. The present study evaluates the role of sarcopenia as a predictor of ERCP-related outcomes in a cohort of elderly patients. Methods: Patients who underwent ERCP between June 2019 and January 2023 were retrospectively included. Demographic and procedure-associated data were collected. Sarcopenia was assessed using the skeletal muscle index (SMI) measured from a single axial slice through the L3 vertebra on a CT scan. ERCP-related outcomes were recorded. Univariate and multivariate analyses were used to assess the correlation between sarcopenia and procedural outcomes. Results: In total, 256 patients were enrolled, of whom 30 (11.7%) were sarcopenic. Cardiopulmonary complications of ERCP occurred in 3.5%. Sarcopenia was associated with higher 30-day and 12-month post-ERCP mortality (OR 3.45, p = 0.03; OR 3.87, p = 0.004) and longer hospitalization time (7 vs. 11 days, p = 0.003). Conclusions: SMI is an easy and objective index of sarcopenia that could be used to predict ERCP outcomes. Indeed, sarcopenia was independently associated with prolonged hospitalization and increased mortality in a retrospective cohort of elderly patients.